Utilization of the prevention of parent-to-child transmission of HIV (PPTCT) services in a tertiary care hospital, Odisha, India (Bangladesh Journal of Medical Science, 2014)
Aims: To assess seroprevalence of HIV among antenatal women and the extent of utilization of interventions to minimize the risk of mother-to-child transmission. Study Design: Descriptive cross-sectional study was carried out among antenatal women who attended integrated counseling and testing center (ICTC) of HIV. Sample sizes were determined from the number of pregnant women that attended ICTC. Place and Duration of Study: Data and samples were collected from a tertiary care hospital, Odisha, India during January 2009 to December 2012. Methodology: All pregnant women were counseled and tested for HIV by rapid test. All HIV-seropositive antenatal women (ANW) were linked to services and followed up for institutional delivery, single-dose nevirapine (sdNVP) prophylaxis, infant feeding options and testing of children at 18 months. Results: Out of 11,508 ANW registered and pretest counseled, 11,390 (98.97%) accepted HIV testing. Sixty women were found to be seropositive, thus showed seroprevalence rate of 0.53% (60/11,390). CD4 testing was carried out in all ANW and five (8.33%) were eligible for antiretroviral therapy (ART). Seven (11.67%) had opted for medical termination of pregnancy (MTP). All 48 ANW delivered institutionally, only 7 (14.58%) received cesarean delivery. Out of 46 live births, 5 (10.87%) ANW were on ART, 35/41 (85.37%) received sdNVP mother baby-pair prophylaxis and only 8/46 (17.39%) mother opted for replacement feeding. Twenty one children have reached 18 months till date and among them three (14.29%) were HIV-seropositive. All three were delivered vaginally, received sdNVP prophylaxis and were exclusively breast fed for 6 months. Conclusion: The HIV-seroprevalence rate among antenatal women was 0.53% and mother-to-child transmission (MTCT) rate was 14.29%. Reduction in MTCT rate needs pre or early antenatal HIV testing, prenatal antiretroviral medication, preference for cesarean delivery, 100% antiretroviral prophylaxis coverage and education on avoidance of breast-feeding. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18300 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.163-169